How the library can improve students' information retrieval skills? (Journal of EAHIL, 2023)
Good skills in information retrieval play an important role in studies. This article describes how the library can strengthen students' information retrieval skills by providing different kind of services. This article focuses in particular on students studying at the LAB University of Applied Sciences’ Master’s degree programmes in social and health care. The development of services was based on a study of library services by means of service design.